Millennial Generation Strategy in Agricultural Development and Rural Economy with Technology - Nu'man Afif; Ahmad Ulil Albab Al Umar; Fatimah Malini Lubis; Ita Soegiarto; Pawisari Pawisari (ProBisnis : Jurnal Manajemen, 2023)
The future of agriculture in Indonesia is currently threatened with the diminishing interest of the younger generation to engage in agriculture. Because it contributes greatly to the development of the national economy if it is supported by productive and quality human resources. The purpose of this study is to find opportunities and development prospects for agriculture and the economy in rural areas with technology by the millennial generation. This research is a type of qualitative research with basic research and data and information analysis using scientific review. In the agricultural sector we are currently facing, one of which is the workforce in the agricultural sector which is dominated by workers who are no longer productive. Village development and economy will depend heavily on productive workers, so that when there is no more young generation, agricultural needs will definitely be supplied from outside. With technology and information, people can easily find and manage an activity not in agriculture. In agriculture, technology can be applied as a means or trick to improve farming.